LATAR BELAKANG PREDESTINASI GANDA JOHN CALVIN: “Historis Kemunculan Predestinasi Abad ke-4 hingga ke Masa Calvin” - Pangeran Manurung (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2021)
The problem in this paper lies in the theological issue of predestination, especially regarding the history of calculating the calvin's version of double predestination. The emergence of the concept of the choice of God over some has created complex theological problems because it was interpreted differently by Calvin's successors. This discussion aims to examine the background to why Calvin taught the extreme predestination formula. Because it focuses on the issue of "background", this paper uses a historical literature research approach. This paper will describe the history of the concept of predestination before Calvin and examine the historical circumstances at the time this formula was presented. As a result, Calvin's version of predestination lived in the 16th century, starting with the ideas of Augustine in the 4th century. The conclusion of the paper proves that Calvin's predestination will be misunderstood if it directly interprets the Predestination text from a theological aspect and ignores social reasons and personal experiences of Augustine and Calvin. Calvin's predestination cannot be separated from the historical-social aspects of the 16th and 4th centuries.